Etika dan Regulasi Penggunaan Large Language Models dalam Praktik Hukum di Indonesia - Ayun Hapsari; Mawardi (Sah Publisher, 2026)
The use of Large Language Models in legal practice in Indonesia is increasing in line with the digitalization of legal services and the development of artificial intelligence. The main issues that arise relate to the compatibility of such technology use with the ethical principles of the legal profession, as well as the adequacy of the national regulatory framework in governing it. This study employs a normative juridical method with a statutory approach and a conceptual approach through analysis of legal norms, artificial-intelligence ethics policies, and legal doctrine. The findings show that Large Language Models offer benefits in improving efficiency and access to legal information, but also pose ethical risks in the form of algorithmic bias, misinterpretation of norms, and potential violations of confidentiality and data protection. The existing regulatory framework remains general in nature and has not yet specifically regulated the use of Large Language Models in legal practice. Therefore, strengthening regulations and developing specific ethical guidelines are necessary to ensure that the use of Large Language Models remains aligned with professional responsibility, the principle of prudence, and justice in legal practice in Indonesia.